THE IRRESISTIBLE ROLE OF THE DICTIONARIES IN LEARNING LANGUAGES. - Ruziyev Qodir Turdiyevich (Western European Studies, 2024)
Although we are living in a period of highly developed technological age, learning languages still demand much effort and has its own challenges. Learning foreign languages is one of the time consuming As Uzbek language is being used larger and larger year by year, perfect bilingual or talking dictionaries are in great demand among students and tourists and scientists too. In this article I want to discuss about Uzbek and other languages dictionaries especially, Uzbek – English dictionaries and vice versa. Besides these, we’ll also discuss a bit about electronic dictionaries
Keywords: languages; especially; dictionaries; developed